Effects Of Salinity, Light And Nutrients On The Specific Growth Rate, Pigment Content And Total Soluble Protein Of Gracilaria Manilaensis (Yamamoto & Trono, 1994) - Joniyas, Alireza (2016)
Gracilaria is a genus of red algae (Rhodophyta) which is an important raw material for agar industry and some other industries. Demand on the Gracilaria is high, but the wild stock became lesser due to over harvest. To culture this species on a commercial scale, environmental parameters that effect its growth must be well understood. In this study, the effect of salinity, light intensity and quality, photoperiod, and nutrient content on the growth, pigment content (chlorophyll a.